Exploring Nejatullah Siddiqi’s Contribution to the Maqāṣid al-Sharī‘ah in Urdu Literature - Tauseef Ahmad Parray (International Institute of Islamic Thought, 2017)
This paper examines the maqāṣid al-Sharī‘ah discourse with special reference to the contribution of Muhammad Nejatullah Siddiqi (b.1931), India’s renowned Islamic economist and scholar. It describes and analyzes his approach and methodology in debating, discussing, and addressing this discourse, especially its applications and understanding as well as its position and perspective vis-à-vis the contemporary issues facing the global Muslim community. The primary focus is his stance on the modern-day concerns related to and discussed within the paradigm of the maqāṣid al-Sharī‘ah discourse (e.g., ijtihād’s importance and scope, Muslim minorities, and issues ranging from globalization to weapons of mass destruction) within the context of Urdu literature.